Comparison of the Effect of Xylitol Gum- and Masticchewing on the Remineralization Rate of Caries-like Lesions - M. Biria; B. Malekafzali; V. Kamel (Tehran University of Medical Sciences, 2009)
Objective: The use of sugar-free chewing gums has been reported to be highly effective in the prevention of dental caries. This study carried out to compare the effect of mastic gum and a xylitol chewing gum on remineralization of caries-like lesions. Materials and Methods: In this cross-over, single blinded, in situ study, first, artificial caries-like lesions were created in six extracted human premolars. Then axial sections were cut from each tooth to the thickness of approximately 100 microns. Fifteen adult subjects participated in the study. Lower removable appliances with rectangular boxes in the lingual surfaces were fabricated for them. One tooth section was placed in each of these boxes. The appliances were worn for two separate periods of three weeks each. The subjects chewed five sticks of gum (mastic gum and or xylitol chewing gum) per day, each for 20 minutes. In the second period, the sections were replaced with new ones and the participants were instructed to change their gums. The sections were examined by polarized light microscope and the difference between the size of demineralized areas before and after intervention were recorded. Paired t-test and LSD test served for statistical analyses. Results: The decrease in demineralized surfaces in both groups was statistically significant (mastic gum: P=0.018, xylitol gum: P<0.001). The difference of average decrease between the two groups, however, was not statistically significant (P>0.05). Conclusion: Chewing both mastic gum and xylitol chewing gum improved the remineralization of caries-like lesions but their effects were similar.